An Analysis of Jargon used by Asian Comic Writers - Ignasius De Igo Nilan; Agustinus Hary Setyawan (Linguistic, English Education and Art (LEEA) Journal, 2024)
This research aims to find out the jargon used by comic writers as a social group. This research was applying the qualitative descriptive method to collect data. The method used to analyze the meaning and function of jargon is descriptive analysis which is visible in each paragraph. Collecting data was carried out by finding out the jargon on Asian comics such as manga, manhwa, and manhua on the website. The results of this research show the meaning and function of jargon used by comic writers. Jargon is a variety of language which is used by certain social groups or professions and is not understood by other groups. Research regarding the use of jargon in Asian comics can be conclude that jargon is used by comic writers to describe their work. The jargon found is in the form of words, phrases, acronyms, and abbreviations. The function of jargon used by comic writers is to identify and describe the word. This research proves that the use of jargon is not only in other communities but also in the comic writing community. The weakness of this research is that some comics still use Chinese, Korean, and Japanese terms. This is because there are no equivalent English words that is suitable to describe it. The words are dantian, qi, and mana. Researcher hope this writing can be a reference for future researchers to do a researching in other aspects of comics relate with linguistics or language learning media. Keywords: Asian Comics, Comics Writer, Jargon, Language Variety, Sociolinguistic